KREATIVITAS PESERTA DIDIK DALAM PEMBELAJARAN BAHASA INDONESIA MATERI PENCEGAHAN PERUNDUNGAN DENGAN PIXTON - Angela Putri Rizka Sabarudin; Candra Utama; Elly Fithriyanasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students can increase their capacity for self-expression and creative thinking by learning Indonesian. Therefore, to increase students' creative thinking capacity, technology must be incorporated into the language learning process when learning Indonesian. The aim of this research is to increase students' creativity in obtaining bullying prevention material in Indonesian via Pixton. This research uses quantitative descriptive methods, quantitative data analysis and descriptive statistics. Research findings show that students can express their ideas through storytelling, with a score of 96% in the very good category; they can also do this by creating work with a score of 84% in the good category; they can create stories and take action to prevent bullying, with a score of 65% in the quite good category; and they were given the freedom to use their imagination to solve problems, with a score of 70% in the quite good category. Therefore, it can be said that Pixton media can help students be more creative when learning about bullying in Indonesian.